Analyzing the MERS disease control strategy through an optimal control problem - Aldila, Dipo; Padma, Herningtyas; Khotimah, Khusnul; Desjwiandra, Bevina; Tasman, Hengki (Zielona Góra: Uniwersytet Zielonogórski)
A deterministic mathematical model of the Middle East respiratory syndrome (MERS) disease is introduced. Medical masks, supportive care treatment and a government campaign about the importance of medical masks will be involved in the model as time dependent variables. The problem is formulated as an optimal control one to minimize the number of infected people and keep the intervention costs as low as possible. Assuming that all control variables are constant, we find a disease free equilibrium point and an endemic equilibrium point explicitly.
Keywords: MERS; medical mask; supportive care; campaign; basic reproduction number; optimal control